Simulação de dano parcial em sementes e sua relação com o desenvolvimento das plântulas de Eugenia spp. - Gasparini, Isabela da Costa (Universidade Federal de São Carlos, 2021)
Seed predation is usually seen as a synonym of death to the seed. Nowadays, it’s known that some damaged seeds can still germinate, and grow as seedlings. In this study we used seeds from Eugenia pyriformis, E. involucrata and E. uniflora to: (i) to test what is the threshold of damage the seeds can tolerate and if tolerance is linked with seed size; (ii) to evaluate the viability of these seedlings, considering the gap of information about the late effects of partial predation; (iii) to investigate if seed damage affect resource allocation to the roots or stem. Seeds were damaged to simulate the partial consumption by a rodent. The seedlings were planted in tubes and kept in a greenhouse for three months. Seedlings emerging from large seeds, represented by E. pyriformis, were not affected by light damages, and light damages stimulated seedling growth. Seedlings from small seeded plants were more affected by damages, resulting in smaller seedlings. Seedlings from E. uniflora invested more in root growth, while E.involucrata invested more in stem growth. Our results indicate that partial damage to the seeds are relatively well tolerated by Eugenia, and that, when non-extensive, these damages can contribute for a faster seedling development.
Simulation of partial damage in seeds and their relationship with the development of Eugenia spp seedlings
Keywords: Dano parcial; Ecologia de plantas; Granivoria; Myrtaceae; Predação de sementes; Partial damage; Granivory; Myrtaceae; Plant ecology; Seed predation; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS